HMGB1 Mediated Inflammation and Autophagy Contribute to Endometriosis - Huang, Jingying; Chen, Xuan; Lv, Yuchun (Frontiers in Endocrinology, 2021)
Aim: High mobility group box (HMGB)-1 has been implicated in endometriosis due to the important regulatory roles of inflammation in endometriosis. The aim of the present study was to explore the roles of HMGB-1 in endometriosis and to elucidate the underlying mechanism. Methods: Endometrial specimens were collected from women with endometriosis and healthy volunteers. Immunohistochemistry staining was used to determine the expression patterns and localization of HMGB-1 in the normal, eutopic and ectopic endometrial tissues. Western blotting and qRT-PCR were used to determine the mRNA and protein levels of inflammatory cytokines [interleukin (IL)-6, tumor necrosis factor (TNF)-α and IL-1β], autophagy-related markers [beclin-1, autophagy-related (atg)13, microtubule-associated protein light chain (LC)3-I, LC-II and p62] and HMGB-1, respectively. Spearman’s rank correlation analysis was employed to investigate the correlation between HMGB-1 with inflammatory cytokines and beclin-1. Besides, human endometrial stromal cells (HESCs) were isolated from ectopic endometrium and subsequently transfected with shRNA against HMGB-1. After the transfected cells were subjected to hypoxia, ELISA was used to determine the levels of HMGB-1 and inflammatory cytokines in the cell supernatant. Western blotting was used to determine the expression levels of autophagy-related markers in the cells. Results: Positive correlations were observed between HMGB-1 and the inflammatory cytokines. In addition, a positive correlation was also identified between HMGB-1 and beclin-1 in the ectopic endometrium. Further results demonstrated that autophagy-related markers beclin-1, atg13 and p62 were significantly upregulated in the ectopic endometrium. In addition, HMGB-1 knockdown suppressed the levels of inflammatory cytokines IL-6, TNF-α and IL-1β and autophagy-related markers beclin-1 and atg13, while upregulated p62 in HESCs under hypoxic condition. Conclusion: Knockdown of HMGB-1 under hypoxic condition regulated inflammatory cytokines and autophagy-related markers. HMGB-1 might contribute to the development of endometriosis in part through regulating inflammatory response and autophagy.